Career Skills Of Minang Ethnic As Street Vendors In Padang City And Implications In Guidance Counseling - Murisal, Murisal; Dewita, Erna; Safitri, Elvi; Maiseptian, Fadil; Deswila, Nurhamsi (Universitas Ahmad Dahlan, 2023)
The development of the retail business that has penetrated Indonesia, including West Sumatra has spurred the expertise of the Minang ethnic as street vendors. This study aimed to determine the career expertise of street vendors and the factors that influence it in the city of Padang, West Sumatera. The method used in this research is descriptive qualitative with a case study approach to street vendors in Padang City. The data was taken in 2021 by using purposive sampling technique. The subjects in this study consisted of three street vendors and additional informants which were government officials and close friends. The result of the study revealed that career skills of Minang ethnicity are different in each subject. In the career exploration aspect, the subject is able to utilize various sources of information about the world of work in contrast to other subjects, only learning with the environment without utilizing various sources of information for work and potential sources such as counseling counselor. Furthermore, in the aspect of making career decisions, all subjects have good ability in making decisions, it's just that as traders it is necessary for the three subjects to make clear bookkeeping to facilitate the progress of their merchandise. Also, environmental factors, including the culture of the Minang ethnic itself has influenced the career expertise of street vendors in the city of Padang. For this reason, it is necessary to increase the knowledge and skills of Minang ethnic street vendors.